Peirce Polymath (Nóema, 2024)
We present succinctly Peirce’s extremely diversified works in mathematics and logic, trying to underline both their differential specificities and their integral connections. As a result, the global understanding of Peirce as a polymath is also reflected in its local mathematical architecture.